The crystalline waters of the Bodoquena Plateau revealed Hypostomus froehlichi (Siluriformes: Loricariidae), a new armored catfish from the rio Paraguay basin in Brazil - Zawadzki, Cláudio H.; Nardi, Gabriela; Tencatt, Luiz Fernando Caserta (Zootaxa, 2021)
The menaced and poorly-known waters of the Bodoquena Plateau revealed a new resident, the stunning Hypostomus froehlichi sp. n., a large-sized armored catfish, which is finally described after more than twenty years since its discovery. The Bodoquena Plateau is drained by the rio Paraguay basin, and is located in the state of Mato Grosso do Sul, Brazil. The new species differs from its congeners on the Bodoquena crystalline waters by having teeth with morphological and numerical variation in adult specimens. There is a continuous range of specimens having about 20 thick and worn teeth to specimens having about 50 thin teeth with intact crowns and lanceolate main cusps. Additional diagnostic characters are: dentaries angled more than 90 degrees, dark blotches, one plate bordering supraoccipital, moderate keel along dorsal series of plates, usually two rows of blotches per interradial membrane on dorsal, pectoral and ventral fins, and by attaining comparatively large size. Hypostomus froehlichi seems to be endemic to the area of the Bodoquena Plateau, in rivers draining to the rio Miranda. The description of the new species reveals a potential conservation flagship species as it is one of the most seen and documented fish by visitors and divers in the clear waters from the touristic, though menaced, Bonito region in Brazil.